2020
DOI: 10.1055/a-1072-5207
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at a Small Brain: Transnuchal Ultrasound Facilitates High-Resolution Imaging of the Cerebellum in Preterm Infants

Abstract: Purpose Very preterm infants are at risk for cerebellar injury and impaired cerebellar growth with adverse neurodevelopmental outcome. Ultrasound through the mastoid fontanel (MF) with a curved-array or sector probe is the most established method for the sonographic examination of the cerebellum. The goal of our study was to examine the validity of transnuchal ultrasound through the foramen occipitale magnum (FOM) with a linear probe for monitoring postnatal cerebellar growth. Methods Retrospective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The best acoustic window to study the posterior fossa is usually represented by the mastoid fontanel (MF; Buckley et al, 1997;Luna and Goldstein, 2000;Steggerda et al, 2015). However, a recent study carried out by Muehlbacher et al (2020) encouraged the approach through the Foramen occipital magnum (FOM) in very low birth weight infants. The FOM window allows to examine both hemispheres at the same time and easily detect even small cerebellar damages.…”
Section: Other Neuroimaging Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The best acoustic window to study the posterior fossa is usually represented by the mastoid fontanel (MF; Buckley et al, 1997;Luna and Goldstein, 2000;Steggerda et al, 2015). However, a recent study carried out by Muehlbacher et al (2020) encouraged the approach through the Foramen occipital magnum (FOM) in very low birth weight infants. The FOM window allows to examine both hemispheres at the same time and easily detect even small cerebellar damages.…”
Section: Other Neuroimaging Techniquesmentioning
confidence: 99%
“…The FOM window allows to examine both hemispheres at the same time and easily detect even small cerebellar damages. Therefore, this approach must be considered, especially in very preterm infants (Muehlbacher et al, 2020). Particularly in this specific population, different studies proved that cUS, though unable to detect cerebellar microhemorrhages, plays an important role in revealing massive cerebellar ones, severe conditions potentially leading to cerebellar disruption and eventual atrophy, with subsequent long-term pervasive neurodevelopmental impairments, involving cognitive, learning, and behavioral areas (Limperopoulos et al, 2005(Limperopoulos et al, , 2007Parodi et al, 2015).…”
Section: Other Neuroimaging Techniquesmentioning
confidence: 99%
“…The results showed that after adjusting for head shape, there were no significant differences between the two groups, indicating that even the smallest preterm infants could maintain certain stability in cerebellar growth. Muehlbacher and others retrospectively analyzed the ultrasound scan data of 105 preterm infants and found that the diameters of the cerebellar hemispheres obtained through the mastoid fontanel and the foramen magnum were highly correlated, showing a close relationship between corrected gestational age and cerebellar growth [ 36 ]. The occipital ultrasound performed through the foramen magnum demonstrated superior image quality and resolution compared to other directions, validating its effectiveness in monitoring postnatal cerebellar growth in preterm infants.…”
Section: Neurodevelopment Evaluation (Structural Morphology)mentioning
confidence: 99%
“…23 The trans-nuchal acoustic window is increasingly recognized as a feasible alternative to visualize the cerebellum in VP infants. 24 Cerebellar hemorrhage can occur in high-risk preterm neonates during the first postnatal week after birth, at the same time as the germinal matrix hemorrhage and intraventricular hemorrhage (GMH-IVH). Most CBHs occur in gray matter (zones 1 and 2), which develops from the germinal cell layers of the rhombic lip during embryogenesis; the exclusive involvement of white matter is uncommon.…”
Section: Cranial Ultrasoundmentioning
confidence: 99%